Perception in context of Chinese and Japanese: the role of language proficiency - Lu, Sa; Ren, Rongxia; Guo, Ting; Tang, Xiaoyu (Frontiers in Psychology, 2025)
IntroductionThe effect of language context on bilinguals has been studied in phonetic production. However, it is still unclear how the language context affects phonetic perception as the level of second language (L2) proficiency increases.MethodsChinese–Japanese auditory cognates were selected to avoid the interference of semantics and font or spelling processing. Low- to high-proficiency Chinese–Japanese bilinguals, as well as Chinese and Japanese monolinguals, were asked to judge whether the initial morpheme of the Chinese or Japanese words was pronounced with the vowels /a/ or /i/ in single- and mixed-language contexts.ResultsThe results found that low-proficiency bilinguals judged vowels faster in the single-language context than in the mixed-language context, whereas high-proficiency bilinguals showed no significant difference between the single- and mixed-language contexts. DiscussionThese results indicate that as language proficiency increases, bilinguals appear to adaptively enhance phonetic perception when faced with different control demands in single-language and mixed-language contexts.